(untitled) (Revista Rupturas, 2026)
This text analyzes the inclusion/exclusion dichotomy in the context of the experiences of rural people in the Huetar Norte region of Costa Rica. It is based on a qualitative approach, with a design derived from action research. The study involved 15 people from communities in the cantons of Upala and Los Chiles, as well as two officials from government institutions. The main findings reveal a dialectic of inclusion and exclusion within the framework of neoliberal logic, which catalyzes processes of inequality, territorial tensions, and symbolic devaluation. Despite this, stories of resistance emerge from community activities, inviting us to comprehensively rethink the category of rurality, the subjectivities framed within it, and its transformative power.